Decreased sensitivity of tree growth to temperature in Southeast China after the 1976/’77 regime shift in Pacific climate - Xiaochun, Wang; Zongshan, Li; Keping, Ma (Universiti Kebangsaan Malaysia, 2014)
The climatic regime shift that occurred in the North Pacific Basin during 1976/’77 have been linked to a decadal mode of climate variability, which long-term behavior could be reconstructed from tree-ring records. We analyzed radial growth patterns of five subtropical tree species in Southeast China in relation to air and sea surface temperature, the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) indices 25 years before and after 1977. In 1953-1977, tree-ring chronologies showed higher correlations with air temperature than in 1978-2002, so that their time-series graphs showed divergence after 1977. The first principal component of the five tree-ring chronologies was significantly correlated with ENSO and PDO indices in 1978-2002, while it had no significant correlations with these variables during 1953-1977. Correlation maps of PC1, PDO and ENSO indices with surface air temperature showed different patterns before and after 1977. Based on these comparisons, altered sensitivity of tree growth to temperature in recent decades could depend on basin-wide climatic shift in the North Pacific, which either changed the effects of local climatic factors on tree growth or modified the relationships between local and regional climate.